Bioinspired supramolecular engineering of self-assembling immunofibers for high affinity binding of immunoglobulin G. (September 2018) - Li, Yi; Lock, Lye Lin; Wang, Yuzhu; Ou, Shih-Hao; Stern, David; Schön, Arne; Freire, Ernesto; Xu, Xuankuo; Ghose, Sanchayita; Li, Zheng Jian; Cui, Honggang
Abstract: Many one-dimensional (1D) nanostructures are constructed by self-assembly of peptides or peptide conjugates containing a short β -sheet sequence as the core building motif essential for the intermolecular hydrogen bonding that promotes directional, anisotropic growth of the resultant assemblies. While this molecular engineering strategy has led to the successful production of a plethora of bioactive filamentous β -sheet assemblies for interfacing with biomolecules and cells, concerns associated with effective presentation of α -helical epitopes and their function preservation have yet to be resolved. In this context, we report on the direct conjugation of the protein A mimicking peptide Z33, a motif containing two α -helices, to linear hydrocarbons to create self-assembling immuno-amphiphiles (IAs). Our results suggest that the resulting amphiphilic peptides can, despite lacking the essential β -sheet segment, effectively associate under physiological conditions into supramolecular immunofibers (IFs) while preserving their native α -helical conformation. Isothermal titration calorimetry (ITC) measurements confirmed that these self-assembling immunofibers can bind to the human immunoglobulin G class 1 (IgG1) with high specificity at pH 7.4, but with significantly weakened binding at pH 2.8. We further demonstrated the accessibility of Z33 ligand in the immunofibers using transmission electron microscopy (TEM) and confocal imaging. We believe these results shed important light into the supramolecular engineering of α -helical peptides into filamentous assemblies that may possess an important potential for antibody isolation.